Comprehensive analysis of differentially expressed miRNAs in mice with kidney injury induced by chronic intermittent hypoxia - Su, Yunan; Li, Chaowei; Liu, Weifeng; Liu, Yibin; Li, Liangyi; Chen, Qingshi (Frontiers in Genetics, 2022)
miRNAs have been reported to participate in various diseases. Nevertheless, the expression patterns of miRNA in obstructive sleep apnea (OSA)-induced kidney injury remain poorly characterized. In the current study, miRNA sequencing (miRNA-seq) was conducted to investigate miRNA expression profiles in chronic intermittent hypoxia (CIH)-induced renal injury mouse model. The mouse model of CIH was established. Differentially expressed miRNAs (DEmiRs) were detected using miRNA-seq technology. The sequencing data were subjected to Gene Ontology (GO) functional enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses by the use of a bioinformatics approach. RT-qPCR was further used to evaluate the sequencing results. Finally, we created a network for clarifying the relationship between the miRNAs and target genes. In total, 9 miRNAs were identified to be up-regulated and 9 to be down-regulated in a mouse model of renal injury induced by CIH. KEGG analyses revealed that the Wnt signaling pathway was involved in the development of CIH-induced renal injury. Subsequently, the expression of 8 DEmiRs, namely, mmu-miR-486b-3p, mmu-miR-215-5p, mmu-miR-212-3p, mmu-miR-344-3p, mmu-miR-181b-1-3p, mmu-miR-467a-3p, mmu-miR-467d-3p, and mmu-miR-96-5p, showed a similar trend of expression when verified using RT-qPCR. Finally, 5 selected DEmiRs were used to construct a miRNA‑mRNA network. In conclusion, a total of 18 DEmiRs were identified in the mouse model of CIH-induced renal injury. These findings advance our understanding of the molecular regulatory mechanisms underlying the pathophysiology of OSA-associated chronic kidney disease.